2021
DOI: 10.3390/ma14195596
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Fatigue Performance of Asphalt Mixture Reinforced by Basalt Fiber

Abstract: Basalt fiber has been widely used in asphalt mixture due to its excellent mechanical properties and good combination with asphalt. In order to systematically evaluate the enhancement effect of basalt fiber on the fatigue performance of the mixtures, gradations of Stone Mastic Asphalt and Superpave with different nominal maximum aggregate sizes, namely SMA-13, SUP-20 and SUP-25, were prepared, and a four-point bending beam fatigue test was adopted under the strain control mode. The fatigue damage mode was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Although the cumulative dissipation energy of BFAM is roughly the same as that of AM, the addition of basalt fiber can enhance and prevent cracks. After the addition of fiber, it can prevent the propagation of original defects (microcracks) in the asphalt mixture and effectively delay the initiation of new cracks [ 14 , 17 , 28 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the cumulative dissipation energy of BFAM is roughly the same as that of AM, the addition of basalt fiber can enhance and prevent cracks. After the addition of fiber, it can prevent the propagation of original defects (microcracks) in the asphalt mixture and effectively delay the initiation of new cracks [ 14 , 17 , 28 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the rate dissipated energy change of asphalt mixture has only two stages, and the third stage does not appear. That is, when the modulus of the asphalt mixture reaches 50%, the failure stage of the asphalt mixture has not been reached [ 17 ]. However, RDEC in the second stage is in a stable state, so the plateau value (PV) is still calculated by using the average value of the change rate of dissipative energy in the second stage (600–1700 Cycles).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, many researchers have studied the high-performance cement mortar materials: Li [ 11 ] studied the mechanical properties of aramid/carbon hybrid fiber-reinforced concrete; Haroon [ 12 ] studied the performance of reinforced concrete beams strengthened with carbon fiber reinforced polymer strips; and Shi [ 13 ] studied the effect of desert sand on the pore structure of fiber reinforced mortar. As for polymer materials, most research has focused on the polymer materials modified with fibers and inorganic materials: Li [ 14 ] studied the anisotropic mechanical response and strain localization of a metallic glassy-fiber-reinforced polyethylene terephthalate fabric; Lionetto [ 15 ] studied carbon fiber reinforced polymers; Park [ 16 ] studied a microwave composite forming process based on a sic mold for manufacturing fiber metal laminate; and Lou [ 17 ] investigated the fatigue performance of an asphalt mixture reinforced by basalt fiber.…”
Section: Introductionmentioning
confidence: 99%